2009
DOI: 10.1016/j.freeradbiomed.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant stress-induced loss of IRS-1 and IRS-2 proteins in rat skeletal muscle: Role of p38 MAPK

Abstract: Oxidative stress is characterized as the imbalance between the cellular production of oxidants and cellular antioxidant defenses and contributes to the development of numerous cardiovascular and metabolic disorders, including hypertension and insulin resistance. The effects of prolonged oxidant stress in vitro on the insulin-dependent glucose transport system in mammalian skeletal muscle are not well understood. The current study examined the in vitro effects of low-level oxidant stress (60-90 μM, H2O2) for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 38 publications
6
94
2
Order By: Relevance
“…However, in rat testis, decreased levels of IRS2 were observed following exposed to oxidative stress induced by bisphenol A (44). Another study demonstrated IRS2 degradation in muscle cells treated with hydrogen peroxide (45). Our data show that IRS2 levels were not affected by APAP in human and mouse hepatocytes, indicating that IRS2 may be more resistant to degradation compared with IRS1 as reported in primary mouse hepatocytes (30).…”
Section: Discussionsupporting
confidence: 68%
“…However, in rat testis, decreased levels of IRS2 were observed following exposed to oxidative stress induced by bisphenol A (44). Another study demonstrated IRS2 degradation in muscle cells treated with hydrogen peroxide (45). Our data show that IRS2 levels were not affected by APAP in human and mouse hepatocytes, indicating that IRS2 may be more resistant to degradation compared with IRS1 as reported in primary mouse hepatocytes (30).…”
Section: Discussionsupporting
confidence: 68%
“…Different levels of IRS1 phosphorylation and activation are key processes that modulate insulin signaling in skeletal muscle (29). The molecules involved in the regulation of oxidative stress have been previously associated with differences in IRS1 activation and expression (30,31). Furthermore, JNK phosphorylation is increased in the skeletal muscle of PRDX6 2/2 mice, and augmented JNK activation can lead to the deregulation of IRS1, as has already been reported in insulin-resistant nonobese subjects (32).…”
Section: Discussionmentioning
confidence: 72%
“…This model of postnatal early overnutrition (EO) was associated with hyperphagia, obesity, hypertension and hyperinsulinemia in adult life [10][11][12][13][14]. Other studies have suggested that oxidative stress, the imbalance between cellular production of reactive oxygen species (ROS) and antioxidant defenses in cells, could be an early event in the development of obesity-related chronic diseases, such as cardiovascular diseases, diabetes mellitus and cancer [15,16]. Nutrient overload and obesity increase ROS generation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%